Redemption as a Transformational Cultic-Pneumatological Act: A Thematic Analysis of Hebrews 9:11–14 - Binsar Pandapotan Silalahi; Rafael Gever Manampiring; Bendnigo Bendnigo; Krisjuliyanto Kogoya; Echang Jhonatan Septianus (Jurnal Ilmiah Tafsir Alkitab, 2026)
This study addresses the tendency toward fragmentation in the study of Hebrews 9:11–14, where cultic, pneumatological, and existential approaches have been developed separately, resulting in an inadequate explanation of the relationship between Christ’s actions and the effect of sanctification. This study aims to formulate an integrative model of atonement through thematic analysis within a systematic theological framework, using exegetical examination as an analytical tool. The novelty of this study lies in the formulation of a relational model that integrates blood, the Spirit, and the purification of the conscience into a single coherent conceptual structure. The results of the study show that redemption in Hebrews 9:11–14 is structured as a cultic-pneumatological act that produces ontological transformation. Its contribution clarifies the reading of the text and provides a conceptual foundation for the development of a soteriology that integrates the legal, cultic, and transformational dimensions.